Farm entrepreneurship among emerging farmers under the land restitution program in Limpopo Province, South Africa - Lesedi Molefe Maesela; Grany Mmatsatsi Senyolo; Abenet Belete (Cogent Social Sciences, 2024)
Entrepreneurship is frequently seen as a motivation to raise people’s standards of living, maintain a healthy economy, and preserve the environment. This paper empirically investigated factors influencing farm entrepreneurship among emerging farmers under the land restitution program in Limpopo Province, South Africa, a topic that has not yet been sufficiently explored. Using a stratified sampling procedure, data was collected using a structured questionnaire from a sample of 200 emerging farmers. The farm entrepreneurship index was created using principal component analysis and used as a dependent variable to determine factors influencing farm entrepreneurship in an OLS model. The results showed that there is low farm entrepreneurship among emerging farmers in Limpopo Province. In addition, farm entrepreneurship is negatively influenced by the age of the farmer, while location, enterprise farming, innovation technology, extension services, market information and farmer association positively influence farm entrepreneurship. The study recommends that government develop policies that focus more on the provision of extension services, the support of farmer associations, skill trainings, market connections and supportive policy environments for the growth of business mindset among the emerging farmers.